The aesthetics of chaos : nonlinear thinking and contemporary literary criticism - Gillespie, Michael Patrick (University Press of Florida, 2003)
"An invigorating (and convincing) challenge to the cornerstone assumptions of virtually all contemporary literary criticism ... this study lays the groundwork for a dynamic new approach to reading literature. Sure to be controversial, its fundamental right-headedness should help to open debate on the nature of literary criticism across numerous disciplines